Brain‐Derived Neurotrophic Factor (BDNF) as a Potential Biomarker in Brain Glioma: A Systematic Review and Meta‐Analysis - Fatemeh Hasani; Mahdi Masrour; Sina Khamaki; Kimia Jazi; Erfan Ghoodjani; Antonio L. Teixeira (Brain and Behavior, 2025)
ABSTRACT Background This systematic review and meta‐analysis evaluates peripheral and CNS BDNF levels in glioma patients. Methods Following PRISMA guidelines, we systematically searched databases for studies measuring BDNF in glioma patients and controls. After screening and data extraction, we conducted quality assessment, meta‐analysis, and meta‐regression. Results Eight studies were included. Meta‐analysis showed significantly reduced plasma BDNF levels in glioma patients versus controls (SMD: −1.0026; 95% CI: [−1.5284, −0.4769], p = 0.0002). High‐grade gliomas had lower plasma BDNF (p = 0.0288). Tissue BDNF levels were higher in glioma patients (SMD: 1.9513; 95% CI: [0.7365, 3.1661], p = 0.0016) and correlated with tumor grade (p = 0.0122). Plasma BDNF levels negatively correlated with patient age (p = 0.0244) and positively with female percentage (p = 0.0007). Conclusion BDNF is a promising biomarker in glioma, showing significant changes in plasma and tissue levels correlating with tumor grade, patient age, and gender.